Pengembangan Sistem Penyewaan Alat Event berbasis Website menggunakan Midtrans Sebagai Integrasi Payment Gateway (Studi Kasus : CV. New Brilla Futura) - M. Attala Reza Syahputra; Bayu Rahayudi; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
CV. New Brilla Futura is one of the companies engaged in the rental of event equipment needs. The business process used to process equipment rental orders, manage rental data, equipment rental transactions, and payments in the form of screenshots of proof of transfer is also done manually where buyers interact using the company's WhatsApp. This is considered less effective and produces invalid reports. Therefore, the development of an information system that is integrated with the Midtrans payment gateway is made which can make it easier for managers and buyers to place orders and manage orders. System development begins with a needs analysis through consultation with stakeholders. After getting the results, a design is made in the form of a sequence diagram, class diagram, physical data model. Then make a prototype to visually describe the system requirements. Implementation of the system in the form of a website-based application using the Laravel framework with integration made to midtrans. System testing is carried out through validation testing and all test cases receive valid status. Usability testing was carried out using the System Usability Scale and obtained an average score of 87.5, meaning that the equipment rental system received Acceptability Range Acceptable status based on a questionnaire survey of 8 respondents.